Two new inherited defects of the thyroxine-binding globulin (TBG) molecule presenting as partial TBG deficiency. - Takamatsu, J (1987)
Serum-denatured TBG (dnTBG) measured in 32 families deficient in native TBG (nTBG) was undetectable in all subjects with complete nTBG deficiency and was high in 2 of 16 families with partial nTBG deficiency. nTBG (in mean micrograms per decaliter +/- SD) in members of the Quebec and Montreal families, respectively were: 258 +/- 54 and 230 in affected men, 747 +/- 190 and 927 +/- 90 in affected women, and 1568 +/- 151 and 1300 +/- 195 in unaffected relatives. Corresponding mean dnTBG levels were: 14.3 +/- 2.9 and 21.3 in affected men, 8.6 +/- 1.0 and 11.6 +/- 3.1 in affected women, and less than 2.1 and less than 2.6 in unaffected relatives. All were euthyroid with normal free thyroxine and thyrotropin levels. In comparison to common type TBG, TBG-Quebec was more heat labile by 10 degrees C and TBG-Montreal by 12 degrees C. The degree of dnTBG elevation and nTBG lability at 37 degrees C were correlated (r = 0.99). Isoelectric focusing showed cathodal shift of all TBG bands: TBG-Quebec by 0.06 isoelectric points (pI) and TBG-Montreal by 0.02 pI. These two TBG variants represent different mutations most likely affecting the polypeptide chain of the molecule. Their inheritance is X-chromosome linked. The instability of these TBGs at 37 degrees C may lead to more rapid degradation in vivo resulting in low nTBG and high dnTBG concentrations in serum.